Reviving lost shadows: investigating the habitat ecology of the rediscovered hispid hare (Caprolagus hispidus) in Nepal - Aakriti Prasai; Bijaya Dhami; Apoorv Saini; Roshna Thapa; Kopila Samant; Krishika Regmi; Rabin Singh Dhami; Bipana Maiya Sadadev; Hari Adhikari (PeerJ, 2024)
The endangered hispid hare (Caprolagus hispidus) is one of the least studied mammal species. The recent rediscovery of hispid hare in Chitwan National Park (CNP) after three decades, necessitated urgent conservation measures. A detailed investigation into the species’ ecology is imperative for developing evidence-based conservation strategies to support these efforts. The main objective of this study is to investigate the current distribution pattern and habitat preferences, offering vital insights for the effective preservation and management of the species and its habitat. Between 28 January and 13 February 2023, fifty-two surveys using strip transects were carried out in the potential areas. If any indirect signs of the presence of the hispid hare were identified, the corresponding value is coded as 1 “used plot”. In contrast, a value of 0 was assigned if there is an absence of any indirect signs “habitat availability plot”. Nine habitat predictors (habitat type, ground cover, distance to water source, distance to roads/path/firelines, ground condition, dominant plant species, presence/absence of (anthropogenic disturbance, predators, and invasive species), were measured from both plot types (“used plot” and “habitat availability plot”). Our research indicates a clumped distribution pattern within the CNP, with the Sukhibhar grassland identified as a key hotspot. Our study reveals the hispid hare’s adaptability to diverse grassland conditions, favoring both tall and short grasslands. It is essential to integrate the species’ preference for various grassland habitats and critical water sources to enhance conservation strategies. This requires a comprehensive grassland management plan for Chitwan National Park that preserves habitat diversity, safeguards key water sources, and adapts to evolving environmental conditions.